Exploring Rhetoric Style of Erwin Smith and Armin Arlert in The Anime Series “ATTACK ON TITAN” - Napitupulu, Agustin Praspinsa; Pasaribu, Arsen Nahum; Sihite, Jubilezer (Universitas Pahlawan Tuanku Tambusai, 2024)
Many scholars have conducted research on rhetorical style. However, there has been limited investigation into this area by individuals. In the past 6 years, research on rhetorical style has gained significant attention, yet discussions surrounding this research remain scarce. This study examines the rhetorical style employed by two central characters in the anime Attack on Titan: Erwin Smith and Armin Arlert. Specifically, it seeks to analyze the application of Aristotle's rhetorical style ethos, pathos, and logos within their dialogues and monologues. Data collection involved the systematic analysis of transcripts from the anime through three steps: (1) viewing the series, (2) identifying instances of ethos, pathos, and logos in relevant scenes and dialogues, and (3) performing a detailed analysis of these rhetorical elements. A total of 276 rhetorical instances were identified across both characters. The most dominant part of the rhetorical style is Pathos used by Erwin Smith, namely 32 occurrences (34.04%). Ethos and Logos have the same results, namely 31 occurrences (32.97%), covering 62 (33.70%) occurrences of Pathos used by Armin Arlert, as well as the results of Ethos and Logos in Armin Arlert which consist of 60 occurrences (32.96%).The findings reveal that Erwin Smith and Armin Arlert employ rhetoric primarily to evoke strong emotional responses and foster audience empathy with the discussed themes. The analysis highlights the effectiveness of their rhetorical styles in achieving persuasive communication within the anime's narrative framework.